2019
DOI: 10.1038/s41560-019-0468-1
|View full text |Cite
|
Sign up to set email alerts
|

Substantial emission reductions from Chinese power plants after the introduction of ultra-low emissions standards

Abstract: In 2014, China introduced an ultra-low emissions (ULE) standards policy for renovating coal-fired power-generating units to limit SO2, NOX and PM emissions to 35, 50 and 10 mg m-3 , respectively. The ULE standard policy had ambitious levels (surpassing those of all other countries) and implementation timeline. We estimate emission reductions associated with the ULE policy by constructing a nationwide, unit-level, hourly-frequency emissions dataset using data from a continuous emission monitoring systems networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
174
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 335 publications
(192 citation statements)
references
References 37 publications
3
174
0
Order By: Relevance
“…Since 2014, all state-monitored companies have been mandated to report their CEMS data to the local governments through a series of online platforms for different provinces (listed in Supplementary Table 1). Local entities have random onsite inspections to check the truthfulness of the reported results on at least a quarterly basis 23,24,28,32,34 ; this system enables a comparison of CEMS data across different firms to explore potential outliers and abnormalities and prevent data manipulation 28,35 . Then, the governments release the inspection results to the public through the same online platforms (listed in Supplementary Table 1) 24,36,37 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2014, all state-monitored companies have been mandated to report their CEMS data to the local governments through a series of online platforms for different provinces (listed in Supplementary Table 1). Local entities have random onsite inspections to check the truthfulness of the reported results on at least a quarterly basis 23,24,28,32,34 ; this system enables a comparison of CEMS data across different firms to explore potential outliers and abnormalities and prevent data manipulation 28,35 . Then, the governments release the inspection results to the public through the same online platforms (listed in Supplementary Table 1) 24,36,37 .…”
Section: Methodsmentioning
confidence: 99%
“…Local entities have random onsite inspections to check the truthfulness of the reported results on at least a quarterly basis 23,24,28,32,34 ; this system enables a comparison of CEMS data across different firms to explore potential outliers and abnormalities and prevent data manipulation 28,35 . Then, the governments release the inspection results to the public through the same online platforms (listed in Supplementary Table 1) 24,36,37 . Severe financial penalties and criminal punishments can be imposed on firms that adopt data manipulation (in terms of deleting, distorting and forging CEMS data, for example) 38,39 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] In China, it can be expected that thermal power will still occupy a large proportion and the ultralow emission transformation of thermal power has achieved certain results. [50] As far as thermal power is concerned, an obvious question is why we do not directly use clean fuels such as natural gas and biomass for boiler heating, and this is mainly because the distribution of industrial boilers is often decentralized. According to the survey (see Note S2 in the Supporting Information), China's industrial boilers' average capacity is 3.2 t h −1 and the proportion of industrial boilers that could be replaced by air-source heat pump boiler is more than 80%.…”
Section: Perspective On Steam Generation Using Air-source Heat Pumpsmentioning
confidence: 99%
“…Additionally, those anthropogenic aerosols emissions are even able to (partly) obscure the sun, as it has been shown that up to 15% of photovoltaic electricity has been "lost" in China between 1960 and 2015 because of the increased air pollution [18]. However, in 2014, China introduced an ultra-low emissions standards policy to limit the emissions of those anthropogenic aerosols [19].…”
Section: Introductionmentioning
confidence: 99%